STUDI PENGELOLAAN OBAT DI PUSKESMAS BOJA 1 KABUPATEN KENDAL TAHUN 2020 - Richa; Margareta Ayu Lestari; Lyla Aprilia; Niken Dyahariesti (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Drug management is an important aspect that affects operational costs in improving the quality of pharmaceutical services at the Puskesmas. The purpose of this study was to determine the efficiency of drug management at the stages of distribution, storage and use at the Boja 1 Public Health Center. This research was a non-experimental study with a descriptive approach. Data collection was taken retrospectively using reporting data for the 2020 period. Data processing was carried out by analyzing and comparing the suitability of the results with the standard indicators of Pudjaningsih (1996) and the Indonesian Ministry of Health (2011). The results of the research at the distribution stage show that the drug distribution system is appropriate. Based on the turn over ratio indicator, the result is 3.2 times, the drug availability indicator is 31.5 months, the percentage of expired drugs is 2% and the dead stock indicator is 32%. At the storage stage the results of the conformity percentage were 78%. At the use stage, the indicator for the average number of drug items was 3.69, the percentage for generic drugs was 62.06%, the percentage for prescribing antibiotics was 12.2% and the percentage for injection was 4.07%. Drug management at the stages of distribution, storage and use at the Boja 1 Health Center is not fully 100% in accordance with the indicator standards.